Pre-Menopausal Women With Breast Cancers Having High AR/ER Ratios in the Context of Higher Circulating Testosterone Tend to Have Poorer Outcomes - Rajarajan, Savitha; Korlimarla, Aruna; Alexander, Annie; Anupama, C. E.; Ramesh, Rakesh; Srinath, B. S.; Sridhar, T. S.; Prabhu, Jyothi S. (Frontiers in Endocrinology, 2021)
Purpose Women with breast tumors with higher expression of AR are in general known to have better survival outcomes while a high AR/ER ratio is associated with poor outcomes in hormone receptor positive breast cancers mostly in post menopausal women. We have evaluated the AR/ER ratio in the context of circulating androgens specifically in patients younger than 50 years most of whom are pre-menopausal and hence have a high estrogenic hormonal milieu. Methods Tumor samples from patients 50 years or younger at first diagnosis were chosen from a larger cohort of 270 patients with median follow-up of 72 months. Expression levels of ER and AR proteins were detected by immunohistochemistry (IHC) and the transcript levels by quantitative PCR. Ciculating levels of total testosterone were estimated from serum samples. A ratio of AR/ER was derived using the transcript levels, and tumors were dichotomized into high and low ratio groups based on the third quartile value. Survival and the prognostic significance of the ratio was compared between the low and high ratio groups in all tumors and also within ER positive tumors. Results were further validated in external datasets (TCGA and METABRIC). Results Eighty-eight (32%) patients were ≤50 years, with 22 having high AR/ER ratio calculated using the transcript levels. Circulating levels of total testosterone were higher in women whose tumors had a high AR/ER ratio (p = 0.02). Tumors with high AR/ER ratio had significantly poorer disease-free survival than those with low AR/ER ratio [HR-2.6 (95% CI-1.02–6.59) p = 0.04]. Evaluation of tumors with high AR/ER ratio within ER positive tumors alone reconfirmed the prognostic relevance of the high AR/ER ratio with a significant hazard ratio of 4.6 (95% CI-1.35–15.37, p = 0.01). Similar trends were observed in the TCGA and METABRIC dataset. Conclusion Our data in pre-menopausal women with breast cancer suggest that it is not merely the presence or absence of AR expression but the relative activity of ER, as well as the hormonal milieu of the patient that determine clinical outcomes, indicating that both context and interactions ultimately influence tumor behavior.